昭和基地におけるVLFエミッションの地上・人工衛星同時観測 : ヒスとオーロラとの関連 - 巻田, 和男; マキタ, カズオ; Makita, Kazuo; 福西, 浩; フクニシ, ヒロシ; Fukunishi, Hiroshi; 芳野, 赳夫; ヨシノ, タケオ; Yoshino, Takeo (国立極地研究所, 1979)
1976年南極昭和基地において,ISIS1,2人工衛星からのVLF観測テータの受信が行われた.これらのVLFエミッションのテータと地上で同時刻に観測されたVLFエミッションおよひオーロラの観測テータとの比較を行った.一般に,ISIS 2が高緯度領域から低緯度領域に移動していくにつれ,ヒスエミッションとソーサーエミッションが順々に観測される.解析結果によると,ヒスエミッション領域からソーサーエミッション領域に移る境界付近か,地上て見られるもっとも低緯度側のオーロラ・アークを通る磁力線の位置に対応していることが明らかになった.地上て観測されたヒスエミッションのスペクトラムと人工衛星て受信されたヒスエミッションのスペクトラムを比較した結果,地上と人工衛星とを磁力線て結んた領域て観測されるヒススペクトラムは似ておらす,むしろ,人工衛星のサフサテライトポイントが,昭和基地と同じ地磁気緯度付近にある時に観測されるヒススペクトラムが互に類似していることがわかった.このことはヒスエミッションが,人工衛星の高度(h=1400 km)から地上まで磁力線に沿って伝搬していないことを示している.Ray pathの計算を行った結果,地上て受信されるヒスエミッションは,人工衛星の高度からノンダクトな伝搬路をとることが推定された. ISIS VLF data were received at Syowa Station, Antarctica in 1976. These data were compared with VLF and auroral data simultaneously observed on the around. In general, hiss and saucer emissions were succesively observed on ISIS 2, when ISIS 2 moved from the polar cap towards the low latitude. It is found that the geomagnetic field lines through a northernmost auroral arc are located between the occurrence regions of hiss and saucer emissions. It is also found that spectra of hiss emissions observed on the ground (Syowa) are not similar to those of VLF emissions observed in the region connected with field line at the satel-lite altitude, but are similar to those of VLF emissions observed near the same geomagnetlc latitude as that of Syowa Station. The result suggests that auroral hiss emissions do not propagate along the geomagnetic field lines from the statellite height (～1400 km) to the ground. The calculation by means of the ray theory suggests that hiss emissions propagate along a non-ducted path from the satellite height to the ground departmental bulletin paper